Faith in the Absence of God (KULT_online, 2009)
In Kommunismus als Religion. Die Intellektuellen und die Oktoberrevolution (Communism As Religion: Intellectuals and the October Revolution), Russian philosopher Michail Ryklin considers first and foremost the aggressive nature of Bolshevist atheism. At the same time, he elucidates how communism, which pretends to be a “scientific ideology”, in fact has an inherently religious character. Against this background, the second part of the book deals with the complex appeal that communism held for Western intellectuals. For his actual analysis, the author studies relevant texts from Jacques Derrida, Bertrand Russell, Walter Benjamin, Arthur Koestler, Lion Feuchtwanger, Bertolt Brecht, and André Gide (beginning with Derrida's “Return from the USSR”) to delineate various perceptions of communism as a religion.